BE PROGRESSIVE THINKERS, USM PRO-CHANCELLOR URGES ASEAN STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Students from ASEAN higher learning institutions who will become leaders of tomorrow are urged to be progressive thinkers who can contribute ideas towards a more sustainable development.